Question

Asked Feb 9, 2019

6 views

f(x)= x and g(x)= the square root of x+1

What is (f+g)(x)?

Step 1

GIven functions f(x) = x and g(x) = √(x+1)

For ...

Tagged in

Find answers to questions asked by student like you

Show more Q&A

Q: Simplify (-2y^4)^2(-2x^3y^2z)^3

A: To simplify (-2y^4)^2(-2x^3y^2z)^3.

Q: O LINES AND FUNCTIONS Combining functions to write a new function that models a re... Leila and her ...

A: The amount saved by Leila,

Q: 121=(4q+5)2

A: To calculate the value of q from the provided equation which is mentioned below,

Q: #18

A: Refer to question 18 to determine whether the graphs with equation x+5y=-6 and y=5x-8 are parallel, ...

Q: 8*2(2+2)

A: To simplify the expression, the PEMDAS rule is used.PEMDAS stands for Parenthesis, Exponents, Multip...

Q: Let f(x) = 4x2 + 6x -5 and simplify f(2+x)

A: The given function is f (x) = 4x2+6x–5.

Q: Solve for x: e^ x^ 2+6 = e^5x

A: Given expression is

Q: The length of the longer leg of a right triangle is 13inches more than three times the length of the...

A: Let the length of shorter leg be x.Then the length of the longer leg will be 13+3x.The length of the...

Q: what is 2-5

A: In this question we have to explain what the value is of 2 - 5